Assessing eHealth skills across Europeans - Rosalía Vicente, M.; Madden, Gary (2017)
The Internet has made health information more assessable to the general public. However, some serious concerns remain about the quality and reliability of that information, and the ability of the population to accurately interpret these data. An important aspect interpreting healthcare information are eHealth skills. To date, the available evidence is usually based on national analyses of composite measures of eHealth skills. To contribute to the debate our paper analyses particular eHealth skills based on data from a pan-European Union data set. In particular, with microdata from a representative sample, five skills are analysed, viz. searching, locating, understanding, evaluating and using online health information. We use a discrete choice model to identify statistical associations between respondent socio-demographic characteristics and skills. Our analysis reveals a complex pattern of eHealth skills is present across socio-demographic groups, with only self-reported health status and Internet experience influential for all skills. This finding suggests that targeted training actions are necessary to improve eHealth kills, with the seniors and the less educated the groups most in need of training.